Coastal Permafrost and Groundwater Discharge Model - Julia A. Guimond (Hydroshare)
This resource expands on previously published FlexPDE code (doi: 10.4211/hs.98d4192a4f8841149e1502f82b777f69) by incorporating text in the code necessary for analyzing groundwater discharge in the coastal zone. Also included are scripts for -4 deg C and -2 degr C initial surface temperature scenarios.